ESG Practices and Financial Performance: A Study of Non-Financial Companies in Indonesia - Asih, Legenda Telaga; Kurniawati, Estetika Mutiaranisa (Journal of Accounting Research, Organization and Economics, 2025)
Objective This study aims to analyze the impact of Environmental, Social, and Governance (ESG) scores on performance of non-financial sector companies listed on the Indonesia Stock Exchange.Design/Methodology The study procedures were carried out using multiple linear regression analysis to examine the impact of ESG scores and each of its pillars on performance. The sample population comprised 60 non-financial sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. Bloomberg's ESG scores and annual reports served as data sources for measuring the study variables.Results The results showed that environmental, social, and aggregate ESG scores had a positive impact on performance. High scores in each pillar showed companies commitment and responsibility beyond financial aspects. However, governance scores showed no significant influence on performance.Research limitations/implications The research is limited by a restricted study period, which subsequently impacts the quantity of firm-year observations available for analysis. This limitation may affect the thoroughness of the results, since an extended time frame could yield a more substantial dataset, providing enhanced insights into patterns and changes throughout various times.Novelty/Originality This research used Bloomberg ESG score in which every data point is weighted in terms of importance and tailored to different industry sectors. Moreover, the use of the Piotroski F-Score for measuring performance enhanced the comprehensiveness of the measurement methods.